2017
DOI: 10.4102/sajp.v73i1.392
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of exercise in office workers with neck pain: A systematic review and meta-analysis

Abstract: BackgroundNon-specific neck pain is a common health problem of global concern for office workers. This systematic review ascertained the latest evidence for the effectiveness of therapeutic exercise versus no therapeutic exercise on reducing neck pain and improving quality of life (QoL) in office workers with non-specific neck pain.MethodSeven electronic databases using keywords, that is, ‘office workers’, ‘non-specific neck pain’, ‘exercise’ and/or ‘exercise therapy’, ‘QoL’, ‘strengthening’, ‘stretching’, ‘en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 41 publications
1
62
0
Order By: Relevance
“…Likewise, in office-workers exercises may alleviate headache [21]. A systematic review and meta-analysis showed that strengthening exercises should be favoured to endurance and stretching exercise for the treatment of NP in officeworkers [22]. An Australian study examined the impact of neck exercises on workplace productivity in monetary terms specific to office-workers within participating companies [23].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, in office-workers exercises may alleviate headache [21]. A systematic review and meta-analysis showed that strengthening exercises should be favoured to endurance and stretching exercise for the treatment of NP in officeworkers [22]. An Australian study examined the impact of neck exercises on workplace productivity in monetary terms specific to office-workers within participating companies [23].…”
Section: Introductionmentioning
confidence: 99%
“…According to the published literatures a single technique did not yield good clinical results no matter coblation or active exercise for chronic neck pain. [26,27] In this study the patient performed active exercise every day after minimally invasive surgery and got long-term pain relief which gave us clear strategy of clinical treatment for patients with discogenic pain. Passive exercise was usually accepted easily by people when they felt uncomfortable in clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical guidelines and systematic reviews provide recommendations based on moderate evidence that "exercise" or "strengthening and endurance" exercise have small to large effects on pain and disability but provide little detail to the type of exercise to be used in clinical practice [4,5,[10][11][12]. The studies cited within these guidelines and systematic reviews describe multiple different exercise training (ET) programmes aimed at improving neuromuscular function or motor capacity of the neck and shoulder musculature.…”
Section: Rationalementioning
confidence: 99%